Enhanced drug delivery to cancer cells through a pH-sensitive polycarbonate platform. (19th December 2022) - Arno, Maria C.; Simpson, Joshua D.; Blackman, Lewis D.; Brannigan, Ruairí P.; Thurecht, Kristofer J.; Dove, Andrew P.
Abstract : In this paper we a report a pH-sensitive polycarbonate conjugated with the anticancer drug camptothecin that shows enhanced drug delivery towards cancer cells. Abstract : Polymer–drug conjugates are widely investigated to enhance the selectivity of therapeutic drugs to cancer cells, as well as increase circulation lifetime and solubility of poorly soluble drugs. In order to direct these structures selectively to cancer cells, targeting agents are often conjugated to the nanoparticle surface as a strategy to limit drug accumulation in non-cancerous cells and therefore reduce systemic toxicity. Here, we report a simple procedure to generate biodegradable polycarbonate graft copolymer nanoparticles that allows for highly efficient conjugation and intracellular release of S -(+)-camptothecin, a topoisomerase I inhibitor widely used in cancer therapy. The drug–polymer conjugate showed strong efficacy in inhibiting cell proliferation across a range of cancer cell lines over non-cancerous phenotypes, as a consequence of the increased intracellular accumulation and subsequent drug release specifically in cancer cells. The enhanced drug delivery towards cancer cells in vitro demonstrates the potential of this platform for selective treatments without the addition of targeting ligands.